Mengidentifikasi Kecenderungan Riset Komunikasi Kesehatan dan Kontribusinya pada Penanganan Pandemi Covid-19 di Indonesia - Yun Fitrahyati Laturrakhmi; Sinta Swastikawara (Jurnal Riset Komunikasi (JURKOM), 2024)
Various previous studies believe that through its inherently applicable nature, health communication research can ideally be easily applied to health practices and policies. On the other hand, several criticisms have emerged that point to the lack of role of communication scholars in responding to various needs in the health context, including in handling pandemics. This research aims to get an overview of the trends in health communication research produced during the COVID-19 pandemic (response to recovery period) in Indonesia. Through mapping these trends, it will be known whether or not there is a contribution made to practice and policy in handling the COVID-19 pandemic in Indonesia. This research was conducted using the quantitative content analysis method on journal articles that have been published in SINTA-accredited communication journals in the last 3 years (from early 2020 to early 2022). In addition, in-depth interviews were also conducted with 2 communication scholars who focus on the development of health communication studies in Indonesia and medical professionals who are directly involved in public relations for the COVID-19 task force to obtain an overview of the relationship between health communication research and the handling of the covid-19 pandemic. The results of this study show that the trend of health communication research is in line with the views of medical professionals who see that health communication is only limited to instruments. Policy making on health communication is still emphasized on the medical role alone so the space for health communication to become one of the contributors to policy making is getting narrower. On the other hand, the role of health communication is very pronounced in the personal aspect, especially in seeing the local wisdom of the community in dealing with the COVID-19 pandemic, so that it is not trapped in general standardization.